Implementation of Digital Invitation by Utilizing Grapes.js for Invitation Design and QR Scanner for Attendance Tracking - Ristian Aditya; Eko Budi Setiawan (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2025)
This research aims to help people manage and organize event invitations by using digital invitations. Many digital invitation platforms still need to improve, especially in design customization and guest attendance recording. Based on interviews with 17 respondents aged 20-30, 70% have used digital invitations before. Still, they feel the existing system could be more optimal in processing attendance and customizing designs according to preferences. Meanwhile, 30% of respondents who have never used digital invitations stated that they are still more comfortable with printed invitations due to their lack of understanding of digital invitation technology and the features it offers. To overcome this problem, this research proposes the development of a digital invitation application that not only supports the creation and distribution of invitations but also features online payment through Midtrans and QR scanners to record attendance more efficiently and use the application. The test results show that 95% of respondents feel that the application speeds up the creation and distribution of invitations, 87% find it helpful with the design customization feature, 96% strongly agree that the attendance confirmation feature makes it easier to manage guests, and 97% state that the payment process through the application is easy to do.